Pemenuhan Hak Pendidikan Bagi Anak Pekerja Migran Indonesia di Klang Lama, Malaysia - Effendi, Tommy; Rahmi, Atikah (Yayasan Rahmat Islamiyah, 2024)
Indonesia has a substantial population of migrant labourers. There is a significant population of Indonesian migrant workers' children residing in this country without legal authorization, enduring challenging living conditions. Education serves as the fundamental basis for shaping a child's character. Nevertheless, it has been discovered that the offspring of Indonesian immigrants lacking crucial documentation continue to be deprived of school, so severely limiting their prospects of pursuing education abroad. In order to accomplish this objective, it is imperative to expedite the development of character education and cultivate a strong feeling of nationalism through the educational system. This initiative aims to deliver character values education to Indonesian migrant children residing in the Klang Lama area of Malaysia. Malaysia has the potential to actively contribute to enhancing the conditions and rights of children belonging to Indonesian migrant workers residing in Malaysia, while also providing support for their education. This study employs empirical juridical methodologies, specifically focusing on research of an empirical juridical nature. National Education serves the purpose of cultivating skills and moulding the character and culture of a respectable nation, with the aim of educating its citizens to become individuals who possess unwavering faith and devotion to God, exhibit noble traits, maintain good health, possess knowledge, demonstrate capability, creativity, independence, and ultimately become democratic and accountable members of society.